Effect of Various Catalysts on Biodiesel Production from Biomass of Freshwater Algae - Ahmad, Farooq; U. Khan, Amin; Yasar, Abdullah (Asian Journal of Chemistry, 2013)
Catalyst selection for transesterification of oil to biodiesel depends on composition of oil and its source. Algal biomass is a cheaper and effective source for this purpose. Chlorella vulgaris, Rhizoclonium hieroglyphicum and mixed algae culture (Microspora sp., Navicula sp., Lyngbya sp., Cladophora sp., Spirogyra sp. and Rhizoclonium sp.) were selected for current study. Several variables such as solvent types (acetone, hexane and methanol), extraction time (60-300 min), molar ratio (1:1, 3:1 and 6:1), catalyst types (Na, NaOH, KOH and H2SO4), catalyst concentration (0.5, 1.0 and 1.5 %) and transesterification reaction time (20-100 min) were used for extraction of oil and biodiesel production. Highest quantity of oil was extracted using hexane as a solvent while highest biodiesel yield (93.93 %) was obtained from transesterification of Chlorella vulgaris oil under 3:1 alcohol to oil molar ratio, Na catalyst (1 %) and 1 h of reaction time. The work investigated that biodiesel properties are comparable to ASTM standards hence it can be used as vehicular fuel.